Keadilan Upah dan Ketidakpastian Akad Pekerja Harian Lepas dalam Perspektif Hukum Ekonomi Syariah - Resti Yuliana; A. Kumedi Ja’far; Apriansyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study is motivated by the structural paradox within Indonesia’s palm oil sector, which serves as a major contributor to national foreign exchange earnings while still relying heavily on Casual Daily Workers (Buruh Harian Lepas/BHL) who live in vulnerable conditions. The disparity between macroeconomic contributions and workers’ welfare has created inequalities that require further examination. This study aims to analyze wage practices and the validity of employment contracts in smallholder plantations in Mekar Harjo Village, Central Lampung, based on the principles of Islamic Economic Law, particularly the aspects of justice (al-‘adl) and adequacy (kifayah). The research employed a qualitative method with a case study approach. Data were collected through participant observation and in-depth interviews with six key informants consisting of workers, landowners, and community leaders. The findings reveal the dominance of oral contracts (mu‘athah) without written agreements, resulting in uncertainty (gharar) and weakening workers’ legal positions. The piece-rate wage system was also found to be highly fluctuating following market prices and often below decent living standards, thereby encouraging the involvement of family members without adequate compensation